Islamic ethical perspective on capital structure, profitability, and firm value: evidence from Indonesia’s healthcare sector - Wati Yaramah; Dewi Rahmahwati (Journal of Islamic Economics Management and Business (JIEMB), 2025)
This study investigates the influence of capital structure, profitability, and firm size on firm value, with dividend policy as a moderating variable, viewed from an Islamic ethical perspective. Using panel data from healthcare companies listed on the Indonesia Stock Exchange during 2019–2023, the research applies multiple regression analysis to examine how financial and ethical dimensions interact in determining corporate value. The results show that capital structure and profitability have a negative and significant effect on firm value, while firm size does not have a significant influence. Dividend policy strengthens the relationship between capital structure and firm value but fails to moderate the effects of profitability and firm size. These findings highlight that excessive leverage and inefficient profit utilization reduce market valuation, whereas transparent dividend distribution enhances investor trust. From the Islamic perspective, these outcomes reflect the ethical principles of ʿadl (justice), amānah (trustworthiness), and ḥikmah (prudence) in managing financial decisions. The study contributes to the integration of ethical considerations into signaling theory and provides practical guidance for corporate managers and policymakers to design balanced financial strategies aligned with Islamic moral accountability.